PENGARUH PUPUK KANDANG AYAM DAN N, P, K TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) DI TANAH ULTISOL - Kasri, Adnan; Khoiri, M. Amrul; ', Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Giving chicken manure fertilizer and N, P, K done to improve the growth and production of sweet corn in ultisol soil.This research aims to obtain interaction of various doses of chicken manure fertilizer and N, P, K the best on the growth and production of sweet corn in ultisol soil. This research was carried out in society garden at Indra Puri, Tenayan Raya District, Pekanbaru in September to December 2013. This research used Randomized Block Design (RBD). The treatment consist of2 factors, factor I: without chicken manure fertilizer, 46,8g/plant chicken manure fertilizer, 70,3g/plant chicken manure fertilizer, 93,7g/plant chicken manure fertilizer and factor II: without giving N, P and K, 9,14g/plant ZA, 6,25g/plant TSP, 0,14g/plant KCl, 13,7g/plant ZA, 9,79g/plant TSP, 0,21g/plant KCl, 18,2g/plant ZA, 13g/plant TSP, 0,29g/plant KCl. Data were analyzed using ANOVA and further tested by Duncan's Multiple test at 5% level. Parameters measured were the plant height(cm), cob diameter (mm), Male flowers appear time (DAP), female flowers appears time (DAP), heavy cob with husk(g), heavy cob without husk (g) and plants dry weight. The results of research shows the interaction of chicken manure fertilizer and N, P, K  had no effect on all parameters except on cob diameter and plants dry weight. Combination treatment of chicken manure fertilizer with N, P, K can improve sweet corn growth, while the increase of sweet corn production occurred at doses 46,8 g/plant chicken manure fertilizer and ZA 13,7 g/plant, TSP 9,79 g/plant, KCl 0,21 g/plant. Keywords: sweet corn, chicken manure fertilizer, N, P, K fertilizer, ultisol soil.